Pengembangan Instrumen Pengukuran Kemampuan Berpikir Kausalitas Peserta Didik pada Mata Pelajaran Sejarah SMA - Auliani Auliani; Ofianto Ofianto; Aisiah Aisiah (RC-INSTITUT, 2019)
This research is based on the unavailability of test questions that can measure the ability to think the causality of learners in understanding the material of learning history. The objective of this research is to develop a valid and reliable test instrument to measure students' sense of causality by following the development step of the ADDIE model. The subject of the validator consists of one historical material expert and one evaluation expert, as well as one subject history teacher from SMA 1 Kubung and one from SMA 1 Bukit Sundi. The subjects of the practicality test of learners amounted to 258 students. The data collection instrument consists of an objective analysis tool of relationships between things and validated validity descriptions and a questionnaire. Data analysis techniques from questionnaires using averages to see the feasibility of products and data test results of the instrument analyzed by the quest program to see the quality of the item. The test results of test instruments according to the assessment of experts in terms of material, language and construction obtained value of 4.77 with very decent category, Validity of the instrument from the validator questionnaire pertained validly. Reliability value 0.77 with a high category. Research findings prove that the test instrument developed able to measure the ability to think the causality of learners.